Critical periodic traveling waves for a periodic and diffusive epidemic model. Issue 10 (27th July 2021) - Zhang, Liang; Wang, Shuang-Ming
ABSTRACT: This work is devoted to the existence of time periodic traveling wave solutions with critical speed c ∗ for a seasonal and diffusive epidemic model. We adopt the approach of super- and sub-solutions and Schauder's fixed point theorem to the truncated problem combined with limiting arguments to obtain the existence of critical periodic traveling waves. This would be appropriate for the modification versions of current model, where standard incidence is replaced by other nonlinear incidence.